Identifikasi Mikroba dari Lendir Estrus dan Deteksi Kebuntingan Sapi Kawin Berulang di Sleman, Yogyakarta - Surya Agus Prihatno; Abdul Samik; Dea Indriani Astuti; Muhammad Agil; Usamah Afiff; Anriansyah Renggaman; Dedi Rahmat Setiadi; Yosua Kristian Adi (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
Repeat breeding is condition of cows that have normal or near normal estrous cycles but fail to become pregnant after several insemination. In this study, we investigated the microbes in the cervical and vaginal mucus of beef cattle and dairy cows that experience repeat breeding and detected the pregnancy after the third or more artificial insemination. A total of 14 beef cattle and 6 dairy cows that experience repeat breeding in the cattle herd in the Yogyakarta region of Indonesia were used as samples in this study. Cervical and vaginal mucus samples were collected using plastic sheet when the cow was re-estrus. The samples were put into the 5 ml Brain Heart Infusion Broth for bacterial isolation and identification. Pregnancy examination was carried out on day 45 after artificial insemination using ultrasound method. Bacteria that could be isolated and identified from cervical mucus and vaginal mucus of beef cattle and dairy cows included Bacillus sp., Staphylococcus epidermidis, Staphylococcus aureus, and Pseudomonas sp. Some cows detected positive in pregnancy examination even though the bacteria were presence in the cervical and/or vaginal mucus. There was various composition of bacteria found in the cervical mucus and vaginal mucus, of beef cattle and dairy cows with repeat breeding in livestock groups in Yogyakarta. The presence of bacterial in the cervical and vaginal mucus during estrus was not always become the causes of failed pregnancy.